Communicating with Extension Clients about Water - Caroline G. Roper; Alexa J. Lamm (EDIS)
As the U.S. and Florida populations continue to increase and the demand for fresh, clean water rises, water quality and quantity issues will become increasingly important. Extension faculty should understand public opinion surrounding water issues and identify the information that needs to be communicated to the public about water issues, as well as the best mode for this communication. This EDIS publication will provide an overview of how to communicate with Florida residents about water, including information about their preferred communication method and what topics surrounding water Florida residents find of interest. This publication will better equip Extension faculty to discuss water quantity and quality issues with Florida residents. This 4-page fact sheet was written by Caroline G. Roper and Alexa J. Lamm, and published by the UF Department of Agricultural Education and Communication, June 2014.